The Effect of the Time Interval Between Radiation and Hyperthermia on Clinical Outcome in 400 Locally Advanced Cervical Carcinoma Patients - Kroesen, M.; Mulder, H. T.; van Holthe, J. M. L.; Aangeenbrug, A. A.; Mens, J. W. M.; van Doorn, H. C.; Paulides, M. M.; Oomen-de Hoop, E.; Vernhout, R. M.; Lutgens, L. C.; van Rhoon, G. C.; Franckena, M. (Frontiers in Oncology, 2019)
Background: Addition of deep hyperthermia to radiotherapy results in improved local control (LC) and overall survival compared to radiotherapy alone in cervical carcinoma patients. Based on preclinical data, the time interval between radiotherapy and hyperthermia is expected to influence treatment outcome. Clinical studies addressing the effect of time interval are sparse. The repercussions for clinical applications are substantial, as the time between radiotherapy and hyperthermia should be kept as short as possible. In this study, we therefore investigated the effect of the time interval between radiotherapy and hyperthermia on treatment outcome. Methods: We analyzed all primary cervical carcinoma patients treated between 1996 and 2016 with thermoradiotherapy at our institute. Data on patients, tumors and treatments were collected, including the thermal dose parameters TRISE and CEM43T90. Follow-up data on tumor status and survival as well as late toxicity were collected. Data was analyzed using Cox proportional hazards analysis and Kaplan Meier analysis. Results: 400 patients were included. Kaplan Meier and univariate Cox analysis showed no effect of the time interval (range 30-230 minutes) on any clinical outcome measure. Besides known prognostic factors, thermal dose parameters TRISE and CEM43T90 had a significant effect on LC. In multivariate analysis, the thermal dose parameter TRISE (HR 0.649; 95% CI 0.501–0.840) and the use of image guided brachytherapy (HR 0.432; 95% CI 0.214–0.972), but not the time interval, were significant predictors of LC and disease specific survival. Conclusions: the time interval between radiotherapy and hyperthermia, up to 4 hours, has no effect on clinical outcome. These results are re-ensuring for our current practice of delivering hyperthermia within maximal 4 hours after radiotherapy.